Addressing the carbon footprint of health organisations: eight lessons for implementation - Kate E Charlesworth; Gregory J Stewart; Peter Sainsbury (Sax Institute, 2019)
Background: The scientific evidence for global warming is overwhelming. Health organisations, as large carbon polluters, are at significant 'carbon risk' and must act to reduce their carbon emissions. Many environmental sustainability initiatives, if properly implemented, would not only reduce harm, waste and pollution but also deliver health, social and financial benefits. Method: We have been involved for more than a decade in efforts to reduce the greenhouse gas emissions of New South Wales (NSW) Health organisations in which we have worked. We draw on our collective experience to offer eight key lessons about implementing environmental sustainability initiatives in health organisations. Results: Sustainability plans have been developed in at least three Area Health Services/Local Health Districts in NSW, but in each case they have been imperfectly implemented. Lessons learnt: Based on our experience, we offer eight key lessons relating to leadership, engagement and developing networks, data, complex adaptive systems, broadening the issue, and political factors.